Psychological and social factors affecting compliance in blood examination and treatment of filariasis.[article]. - Ventura, Elizabeth R.
This study attempted to identify some psychological and situational factors which affect compliance in blood examination and treatment of filariasis. An actual blood survey was undertaken and reasons for accepting and refusing blood examination were determined through interviews. Psychological tests were utilized for identifying personality variables which distinguished acceptors and non-acceptors. It was found out that there were two major reasons for refusing to participate in blood examinations:fear and a perceive lack of a need to have their blood examined. Knowledge attitudes and practices related to the prevention and treatment of filariasis were derived from interviews and an ethnographic study by an anthropologist tests reveal that the typical acceptor is one who is responsible, daring, patient and has an internal locus of control. Recommendations for improving health education and delivery of health services are also discussed.